Estimation of the soil loss in micro watersheds using morphometric analysis and GIS techniques. Issue 1 (June 2020) - Muthukumar, Surya; Ghanesh, Goutham; Balasubramaniam, Prabha; Prasanth; Raghavapriya
Abstract: Remote Sensing (RS) and Geographic Information System (GIS) has now become the fastest growing technology which is found to be useful in many aspects. In current scenario, we face many problems in the form of flood in one side due to improper drainage system and on the other side we face water scarcity. There is a great demand for water at present. This is an ironical situation. As per the rainfall analysis, the amount of rainfall remains same during the years and it is not reduced, but the pattern of rainfall varied greatly. These factors lead to the inefficiency of water storage structures. For that, water resource management has become an inevitable study. RS and GIS acts as a tool used to delineate the watershed. Estimation of Morphometric parameters is done using GIS. Morphometric parameters are of three aspects-Linear aspects, Aerial aspects, Relief aspects. On determining the morphometric parameters, the most eroded region in the watershed is found and for that particular region, run-off is calculated using SCS-CN curve number method. The soil loss is estimated using USLE for the watershed. These techniques are used to find soil loss in the highly eroded sub-watershed in the Noyyal basin. This helps us in estimating the severity of soil erosion and thus a suitable soil - conservation method can be implemented in the watershed